A study of human neutrophil antigen genotype frequencies in Hong Kong. Issue 4 (27th December 2017) - Tam, K.; Tang, I.; Ho, J.; Yeung, W.; Lee, C. K.; Ip, P.; Kwok, J.
SUMMARY: Background: Alloantibodies against human neutrophil antigens (HNA) are associated with a variety of clinical conditions. Over the past decade, the allelic and genotypic frequencies of the five HNA systems have been evaluated. Although the HNA system is less polymorphic than human leukocyte antigens (HLA), significant differences in the genotypic and allele frequencies still exist in different populations, even those living in close proximity. Objectives: To delineate HNA genotypic and allele frequencies to provide vital information on estimating the risk of HNA‐associated diseases for our local population. Methods: Using a validated, in‐house‐developed assay, genotyping for HNA‐1, HNA‐3, HLA‐4 and HNA‐5 was performed on 300 samples from Chinese blood donors from Hong Kong. In addition, the frequency of the HNA‐2 c.843A > T allele was also determined. Results: The allele frequencies of HNA‐1a, ‐1b and ‐1c alleles were 67·8, 31·5 and 0%, respectively, whereas the frequencies of HNA‐3a and HNA‐3b were 71·0 and 29·0%, respectively. The frequencies of HNA‐4a and ‐4b alleles were 99·5 and 0·5%, respectively, and for HNA‐5a and ‐5b, alleles were 85·2 and 14·8%, respectively. Homozygotes for the HNA‐2 c.843 TT variant were absent in our population, whereas only <4% of the population were c.843AT heterozygote carriers. Conclusions: This is the first study to define HNA genotype and allele frequencies using a validated modified in‐house PCR‐SSP method in the Hong Kong Chinese blood donor population. Our approach provides a cost‐effective assay for conducting routine HNA typing and facilitates the incorporation of these assays into routine clinical service. Our results are comparable with those reported in the Guangzhou Chinese population, but the allele frequencies in our Hong Kong Chinese population are significantly different from the reported European frequencies, confirming that a geographical difference exists for HNA allele frequencies.